PERAN DISIPLIN KERJA SEBAGAI MEDIASI KESELAMATAN, KESEHATAN KERJA DAN LINGKUNGAN KERJASERTA DAMPAKNYA TERHADAP PRODUKTIVITAS KARYAWAN PADA MASA PANDEMI COVID-19 DI PERUSAHAAN OTOMOTIF BEKASI - Fitri Rezeki (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Employee work productivity is the success rate of a person in carrying out tasks with predetermined operational standards procedures. The Covid-19 pandemic has an impact on all aspects of human life, at least in the work environment of companies that have to adjust to the current pandemic conditions The number of employees infected with Covid-19 found a decrease in the work productivity of employees who do not follow the operational standards of procedures in work. The purpose of this study was to test how much the role of work discipline in influencing occupational safety & health (OHS) and the work environment and its impact on employee work productivity in automotive companies in Bekasi by involving 73 respondents. The data is then processed with a quantitative approach which is then analyzed by the structure method using smart partial least square (PLS) software. The analysis begins with the testing of variable instruments, the description of variables followed by the feasibility test of the model and ends with hypothesis testing. The results of the study can be concluded that Occupational Safety & Health (OHS) has a direct or indirect effect on the productivity of work. Research has also found the work environment has no direct effect on employee work productivity. Instead, it is mediated by work discipline. And work discipline affects the productivity of employees in bekasi automotive companies.